PENGARUH MODAL KERJA TERHADAP LABA USAHA PADA KOPERASI SERBA USAHA SEJATI MULIA JAKARTA - Anna Nurfarkhana (Sosio e-Kons, 2015)
The purpose of this research is to kmow the effect of working capital with the cooperation efforts provit in the form of the effect income rest. The research method that is used is expose facto. The sample of this research is the member saving data and SHU from 2007 to 2012. The technique of collection data with interview, documentation and literature study. The data analysis technique used is quantitative analysis with regression approach and simple correlation. Based on the result on this research in the working capital effect the effort provit significantly, where 77% of the working capital effects the effort provit. Keyword: working capital, cooperation efforts provit